Political economy of watershed management : policies, institutions, implementation, and livelihoods - Reddy, V. Ratna; Gopinath Reddy, M.; Soussan, John.; Centre for Economic and Social Studies, Hyderabad (Jaipur : Rawat Publications ; Hyderabad : Centre for Economic and Social Studies, 2010)
With reference to Andhra Pradesh, India.
Includes bibliographical references (p. [314]-332) and index.
Keywords: Watershed management -- India -- Andhra Pradesh; Water resources development -- India -- Andhra Pradesh; Rural development projects -- India -- Andhra Pradesh